Fruitvale Station [videorecording (DVD)] - Coogler, Ryan, 1986-; Murray, Chad Michael, 1981-; Spencer, Octavia; Jordan, Michael B. (Michael Bakari), 1987-
The true story of Oscar, a 22-year-old Bay Area resident who wakes up on the morning of December 31, 2008 and feels something in the air. Not sure what it is, he takes it as a sign to get a head start on his resolutions: Being a better son to his mother, being a better partner to his girlfriend, and being a better father to T, their beautiful four-year-old daughter. He starts out well, but as the day goes on, he realizes that change is not going to come easy.